2007
DOI: 10.1507/endocrj.k06-200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Missense Mutation (P366T) of the LHX4 Gene Causes Severe Combined Pituitary Hormone Deficiency with Pituitary Hypoplasia, Ectopic Posterior Lobe and a Poorly Developed Sella Turcica

Abstract: Abstract. LIM homeodomain transcription factors regulate many aspects of development in multicellular organisms. LHX4/Lhx4 is a protein that is essential for pituitary development and motor neuron specification in mammals. In human, a heterozygous splicing mutation of the LHX4 gene was reported in a family with combined pituitary hormone deficiencies (CPHD). In addition to CPHD, these patients were characterized by small sella turcica and chiari malformation. Here we report a Japanese patient with CPHD (GH, PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 24 publications
1
22
1
4
Order By: Relevance
“…7 In addition, ectopic posterior pituitary lobe has been reported in subjects with lim homeobox gene 4 (LHX4) and sry-box 3 gene (SOX3) mutations. 29,30 An ectopic posterior pituitary lobe presents a distinctive appearance on MRI, with the hyperintense posterior lobe characteristically seen at the median eminence in the floor of the third ventricle on unenhanced T1-weighted images. 31 Ectopic neurohypophysis has been rarely reported in association with other cortical malformations.…”
Section: Discussionmentioning
confidence: 99%
“…7 In addition, ectopic posterior pituitary lobe has been reported in subjects with lim homeobox gene 4 (LHX4) and sry-box 3 gene (SOX3) mutations. 29,30 An ectopic posterior pituitary lobe presents a distinctive appearance on MRI, with the hyperintense posterior lobe characteristically seen at the median eminence in the floor of the third ventricle on unenhanced T1-weighted images. 31 Ectopic neurohypophysis has been rarely reported in association with other cortical malformations.…”
Section: Discussionmentioning
confidence: 99%
“…Although a family with GH, TSH, and ACTH deficiency due to a heterozygous mutation in the LHX4 gene has been described, the child was prepubertal, so gonadotropin levels were not investigated [148] . Recently, a second child was reported with a heterozygous LHX4 missense mutation [149] . Theoretically, LHX4 should also cause hypogonadotropic hypogonadism, but no pubertal aged children have yet been described.…”
Section: Sox2 and Sox3mentioning
confidence: 99%
“…A recent analysis suggested that the disease is likely a result of deficits in activation of pituitary genes such as PIT1/POU1F1 rather than a dominant negative effect (15). A second type of patient has a heterozygous mutation (P366T) affecting a residue in the carboxyl terminus of LHX4 (16). This patient has deficiencies of GH, prolactin, TSH, LH, FSH, ACTH, a hypoplastic anterior lobe, an ectopic posterior pituitary, a poorly developed sella turcica, Chiari malformation, and respiratory distress syndrome.…”
mentioning
confidence: 99%